Current and Future Potential Impact of COVID-19 on Kratom (Mitragyna speciosa Korth.) Supply and Use - Singh, Darshan; Brown, Paula N.; Cinosi, Eduardo; Corazza, Ornella; Henningfield, Jack E.; Garcia-Romeu, Albert; McCurdy, Christopher R.; McMahon, Lance R.; Prozialeck, Walter C.; Smith, Kirsten E.; Swogger, Marc T.; Veltri, Charles; et al. (Frontiers in Psychiatry, 2020)
Kratom (Mitragyna speciosa Korth., Rubiaceae) is native to and has traditional use in Southeast Asia. The number of kratom users outside of Southeast Asia has increased significantly in recent decades with use spreading to the Unites States (US) and Europe. Because of its reputed opioid-like psychoactive effects at higher doses, kratom has been regulated in several countries and is subject to an import ban by the US Food and Drug Administration (FDA). Nonetheless, in the US it is estimated that 10-15 million people consume kratom primarily for the self-treatment of pain, psychiatric disorders, to mitigate withdrawal from or dependence on opioids, and to self-treat opioid use disorder (OUD) or other substance use disorders (SUDs). Due to the global COVID-19 pandemic, a shortage in the supply of kratom products may place unexpected burdens on kratom users, potentially influencing some who use kratom for SUD self-treatment to regress to harmful drug use, hence increasing the likelihood of adverse outcomes, including overdose. Inadequate treatment, treatment barriers, and increases in the sales of adulterated kratom products on the internet or in convenience stores could exacerbate circumstances further. Although there are currently no verified indications of kratom scarcity, researchers and clinicians should be aware of and remain vigilant to this unanticipated possibility.